Echocardiographic Study Among Traffic Police Personnel in Central Nepal - Laudari, Shankar; Dallakoti, Samanata; Khanal, Sulav (Journal of National Heart and Lung Society Nepal, 2022)
Background: Echocardiographic studies among traffic police personnel are lacking in the world including in Nepal. So, this study is planned to detect any structural cardiac abnormalities in this specific group population.Methods: This is a cross-sectional descriptive study conducted among fifty traffic police personnel working in the Chitwan district of Nepal. All underwent two-dimensional transthoracic echocardiography in Chitwan Mutu Aspatal. Results: The age ranged from 21 to 55 years, with a mean age of 35 years. Males were predominant (46/50) and 14(28%) were diagnosed as hypertensives. Mild MR was detected on 11(22%) participants.Conclusion: This is the first reported observational study so far among the traffic police personnel in Nepal. There is a high incidence of systemic hypertension among these populations though no major cardiac structural abnormalities were detected.